Pengaruh Terapi Akupresur Terhadap Kualitas Tidur Pasien Pos Operasi Sectio Caesarea Di Rsia Anugerah Medical Center Kota Metro - Rindi Annelia; Sunarsih Sunarsih; Titi Astuti; Al Murhan; Sulastri Sulastri (MAHESA : Malahayati Health Student Journal, 2022)
ABSTRACT Postoperative Sectio Caesarea showed the result of having sleep disturbances. The results of observations of post-operative Sectio Caesarea patients complained of difficulty sleeping due to pain from the surgery, waking up because they wanted to go to the bathroom, waking up to breastfeed, and hearing voices. Action is needed to overcome sleep disturbances after surgery, especially section Caesarea surgery. The purpose of this study was to see the effect of acupressure therapy on the sleep quality of post-section Caesarea patients. This research method uses a group pre-test and post-design. The population in this study was post-operative Sectio Caesarea patients. The sample of this study was 32 respondents who were taken with a non-random sampling technique. The instrument used in this study was a sleep quality questionnaire. The statistical test used in this study wastheWilcoxon signed-rank test. The results showed that the average sleep quality of post operative Sectio Caesarea patients before and after being given acupressure therapy intervention with a difference of -15.00 after statistical test paired sample t-test obtained a p-value (0.000). So there is a difference in sleep quality of postoperative Sectio Caesarea patients after being given acupressure therapy. It is recommended for hospitals to provide therapeutic facilities, especially for post operative sectio caesarian patients, especially those who experience quality sleep. For educational institutions, it is hoped that this research will become a reference and source of information. Further research, further research can examine the effect of acupressure therapy more broadly. Keywords: Acupressure Therapy, Sleep Quality, Post Operative Sectio Caecaera ABSTRAK Post operasi sectiocaesarea menunjukkan adanya hasil yang mengalami gangguan tidur. Hasil observasi pasien post operasi sectiocaesarea mengeluhkan sulit tidur dengan alasan nyeri dibekas operasi, terbangun karna ingin kekamar mandi, terbangun untuk menyusui, mendengar suara. Tindakan diperlukan untuk mengatasi gangguan tidur ssetelah operasi khususnya operasi sectiocaesarea. Tujuan penelitian ini untuk melihat pengaruh terapi akupresur untuk kualitas tidur pasien postsectiocaesarea. Metode penelitian ini menggunakan desain onegrouppretestandpost. Populasi dalam penelitian ini yaitu pasienpost operasi sectiocaesarea di RSIA Anugerah Medical Center Kota Metro. Sampel penelitian ini adalah 32 responden yang diambil dengan teknik sampling non random sampling.  Instrumen yang digunakan pada peneleitian ini adalah lembar kuesioner kualitas tidur. Uji statistik yang digunakan dalam penelitian ini adalah uji wilcoxon signed rank. Hasil penelitian menunjukan bahwa rata-rata kualitas tidur pasien post operasi sectiocaesarea sebelum dan sesudah diberikan intervensi terapi akupresur  dengan pembeda -15.00 setelah dilakukan uji statistik PairedSamle t-test didapatkan nilai p-value (0.000). Maka terdapat perbedaan kualiats tidur pasien post operasi sectio caesarea setelah diberikan terapi akupresur. Disarankan untuk RS memberikan fasilitas terapi khususnya untuk pasien post operasi sectio caesaria khususnya yang mengalami kualitas tidur, Bagi institusi pendidikan diharapkan penelitian ini menjadi referensi dan sumber informasi, Bagi penelitian selanjutnya dapat meneliti lebih luas lagi mengenai pengaruh terapi akupresur. Kata Kunci:Terapi Akupresure, Kualitas Tidur, Post Operasi Seksio Saesarea